Multi-dimensional simulations for extensive off-design conditions of gas turbines by iterative-coupled methods using different characteristic maps of coaxial compressor and turbine - Weimin Deng; Guangming Ren; Linyuan Jia; Zuojun Wei; Yuchun Chen; Xiaohua Gan (Case Studies in Thermal Engineering)
Multi-dimensional simulations offer a complementary numerical platform to gas turbine experimentation, generating supportive data for training adaptation and artificial intelligence models. However, the application of iterative-coupled simulations to extensive off-design conditions depends significantly on the accuracy of generic characteristic maps, particularly near choke and stall regions. In this study, multi-dimensional simulation based on iterative-coupled models using three different sets of maps was developed. Based on experimental speed characteristics data, the standard deviation of performance parameters simulated from the three iterative-coupled models was found to be less than 10−3. Further analysis reveals the convergence consistent traits that the different characteristic maps used in the iterative-coupled simulations only affect convergence speed and scope and do not impact the final convergence results. To apply iterative-coupled simulations to extensive off-design conditions, a self-moving strategy based on the convergence consistent traits of different characteristic maps was developed. The iterative-coupled simulations using the self-moving strategy have an extensive convergence scope, including adjustable-nozzle-area conditions (0.0013–0.008 m2, 78 %–479 %) and adjustable-power-extraction conditions (0–16 kW, 0 %–80 %). This demonstrates that the self-moving strategy for inexact generic characteristic maps can apply iterative-coupled simulations to extensive off-design, compared to the CLM with exact specific characteristic maps.